2017
DOI: 10.1371/journal.pone.0173885
|View full text |Cite
|
Sign up to set email alerts
|

Can volunteering in later life reduce the risk of dementia? A 5-year longitudinal study among volunteering and non-volunteering retired seniors

Abstract: We propose that voluntary work, characterized by social, physical and cognitive activity in later life is associated with fewer cognitive problems and lower dementia rates. We test these assumptions using 3-wave, self-reported, and registry data from the 2010, 2012, and 2014 Swedish National Prescribed Drug Register. We had three groups of seniors in our data: 1) no volunteering (N = 531), 2) discontinuous volunteering (N = 220), and 3) continuous volunteering (N = 250). We conducted a path analysis in Mplus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…Other papers have investigated the ageing workforce and retirement where, for example, voluntary work in later life has been associated with lower self-reported cognitive complaints and a lower risk of dementia. 23 …”
Section: What Has Been Found? Key Findings and Publicationsmentioning
confidence: 99%
“…Other papers have investigated the ageing workforce and retirement where, for example, voluntary work in later life has been associated with lower self-reported cognitive complaints and a lower risk of dementia. 23 …”
Section: What Has Been Found? Key Findings and Publicationsmentioning
confidence: 99%
“…The findings from our study are consistent with previous studies suggesting that engaging in social activities in later life is more likely to prevent the decline of cognitive function at some level, and eventually reduce the risk of mental health problems and its related mortality [ 33 , 34 , 35 ]. Although the positive effects of greater participation in social activities on cognitive impairment in later life have mostly been observed, there are mixed findings on how different social activities impact cognitive function [ 8 , 17 , 34 , 36 ]. For instance, a previous study found that active volunteer work has a protective effect on cognitive function [ 36 ], whereas other studies suggested that active engagement in religious or social group activities contributes to preventing cognitive decline in both middle-aged and older adult populations [ 8 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the positive effects of greater participation in social activities on cognitive impairment in later life have mostly been observed, there are mixed findings on how different social activities impact cognitive function [ 8 , 17 , 34 , 36 ]. For instance, a previous study found that active volunteer work has a protective effect on cognitive function [ 36 ], whereas other studies suggested that active engagement in religious or social group activities contributes to preventing cognitive decline in both middle-aged and older adult populations [ 8 , 37 , 38 ]. In addition, a cross-sectional study examining the relationship between participation in social activities and MMSE decline among Korean middle-aged and older adult populations found that only religious and family-oriented activities were likely to delay cognitive function among individuals over 65, suggesting a community-based policy approach as one of the strategies to prevent and manage the increasing prevalence of dementia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… Systematic review Jenkinson et al, 2013 (+) Our results largely support the assumptions that voluntary work in later life is associated with lower self-reported cognitive complaints and a lower risk for dementia, relative to those who do not engage, or only engage episodically in voluntary work. Population-based cohort study (registry study), n = 1001) Griep et al, 2017 + Volunteering at the initial assessment and volunteering regularly over time independently decreased the risk of cognitive impairment over 14 years, and these findings were maintained independent of known risk factors for cognitive impairment. Panel survey, n = 13,262 Infurna et al, 2016 Socio-economic status + Significant interactions were found between a healthful lifestyle (defined as having more than or equal to three healthful lifestyle factors) and income on changes of global cognition and verbal fluency […].…”
Section: Table A1mentioning
confidence: 99%